Advances in the science of Victorian brown coal - Li, Chun-Zhu (Elsevier, 2004)
Over the past decade, extensive research has been conducted on the subject of coal as one of the worlds leading energy sources. The current and future status of this resource is a topic of considerable interest to the largest world economies, including the US, Japan, China and Europe. Advances in the Science of Victorian Brown Coal provides critical reviews of the information and research published over this time, giving the reader an authoritative overview of the science surrounding this important topic. Critical review of recent research surrounding the utilization of brown coal. Key issues addressed include maximized efficiency and minimized environmental impacts. Focuses on Victorian Brown Coal within the context of biomass and bituminous coal. A critical thermodynamic overview of various advanced power generation technologies.